The social and environmental drivers of corporate credit ratings: international evidence - Gregor Dorfleitner; Johannes Grebler (Business Research, 2020)
We provide evidence of the exogenous impact of environmental and social performance components on credit ratings in North America, Europe, and Asia. In particular, the product innovation dimension is clearly identified as being the dominating driver of credit ratings within the environmental performance in every subsample region. In the social performance dimension, the extent of diversity is a main driver for firms in North America and Europe, but due to cultural reasons, not in Asia. Our results show that the risk mitigation view holds for all significant corporate social or environmental performance variables, but the magnitude of impact differs regionally.
Keywords: 650; Credit risky; CSR; CSP; Asset4; Credit ratings; Sustainability